2015
DOI: 10.3349/ymj.2015.56.3.705
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Brain Activity in Social Reward Learning in Children with Autism Spectrum Disorder: An fMRI Study

Abstract: PurposeWe aimed to determine whether Autism Spectrum Disorder (ASD) would show neural abnormality of the social reward system using functional MRI (fMRI).Materials and Methods27 ASDs and 12 typically developing controls (TDCs) participated in this study. The social reward task was developed, and all participants performed the task during fMRI scanning.ResultsASDs and TDCs with a social reward learning effect were selected on the basis of behavior data. We found significant differences in brain activation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…In addition, significant hyper-connectivity was identified between the left dorsal dysgranular insula and the STG.L in ASD. In line with the hyper-connectivity of our result, previous studies showed increased activity during social reward learning (Choi et al, 2015 ), sentence comprehension task (Just et al, 2004 ), and facial emotion processing (Dalton et al, 2008 ), as well as increased gray matter volume in STG.L in ASD (Waiter et al, 2004 ). Moreover, our finding of functional hyper-connectivity is also supported by the positive correlation with the ADI-R social scores, which implied that children with greater connectivity exhibited more severe impairment in the social domain.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, significant hyper-connectivity was identified between the left dorsal dysgranular insula and the STG.L in ASD. In line with the hyper-connectivity of our result, previous studies showed increased activity during social reward learning (Choi et al, 2015 ), sentence comprehension task (Just et al, 2004 ), and facial emotion processing (Dalton et al, 2008 ), as well as increased gray matter volume in STG.L in ASD (Waiter et al, 2004 ). Moreover, our finding of functional hyper-connectivity is also supported by the positive correlation with the ADI-R social scores, which implied that children with greater connectivity exhibited more severe impairment in the social domain.…”
Section: Discussionsupporting
confidence: 92%
“…Original ture with unreported relevant data from publications on related disorders or tasks. 31,34,45 The existing literature included conflicting results that were difficult to compare owing to varied sample age, different correction methods, and region of interest analyses, which inherently introduce bias. 46 This metaanalysis addressed these issues and revealed that ASD groups showed reward circuitry hypoactivation for both social and nonsocial rewards.…”
Section: Evaluation Of the Social Motivation Hypothesis Of Autismmentioning
confidence: 99%
“…Consistent with this hypothesis, numerous psychological studies have shown diminished sensitivity to the positive reward value of social stimuli in subjects with ASD (Scott‐Van Zeeland et al , ; Chevallier et al , ; Lin et al , ; Sasson et al , ; Dubey et al , ; Kim et al , ). Accordingly, electrophysiological (Stavropoulos and Carver, ; Gonzalez‐Gadea et al , ) and pupillary (Sepeta et al , ) responses as well as neural activation in brain areas involved in reward anticipation and/or processing (notably PFC and NAc) (Scott‐Van Zeeland et al , ; Kohls et al , ; Assaf et al , ; Kohls et al , ; Richey et al , ; Choi et al , ; Leung et al , ) are diminished in ASD patients presented with social stimuli (Figure ). Of note, subjects with ASD also display hypo‐activated NAc and caudate putamen (CPu) while anticipating negative social reinforcement (Damiano et al , ) and diminished activity in the social brain circuitry (including PFC and amygdala) in response to social touch (Kaiser et al , ).…”
Section: Evidence For Blunted Reward Processes In Autism Spectrum Dismentioning
confidence: 99%